Ainsley Harriott's Low-fat Meals in Minutes - Harriott, Ainsley (London BBC Worldwide Limited, 2005)
Bringing us the best in low-fat tasty food, Ainsley Harriott is the master of sensational and speedy cooking. Packed with 80 scrumptious low-fat recipes, from Jalapeno tiger-prawn ginger skewers to Peri peri pork medallions and lemon, Low Fat Meals in Minutes shows that low in fat does not mean low in taste.
Include Colour Illustrations and Index
Designed by Good, Susannah
Keywords: Low-fat diet -- Quick and easy cooking